Pendekatan Matematika Realistik Untuk Meningkatkan Kemampuan Berpikir Matematis Siswa - Nurmudi, Nurmudi (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractThe purpose of this study is to improve students' mathematical thinking skills using a realistic mathematical approach. The research is a Classroom Action Research (CAR) conducted collaboratively and participatively. The subject of the research was the students of class VIII B, State Junior High School 2 Giriwoyo, in the academic year 2017/2018 with 32 students. While the object of research is the whole process of learning mathematics through the application of a realistic mathematical approach implemented in class VIII B of SMP Negeri 2 Giriwoyo. Based on data obtained from observations, field notes, questionnaires, interviews, tests of cycle I and cycle II, as well as documentation, the researcher concludes that mathematics learning activities through the application of a realistic mathematical approach in class VIII B of SMP Negeri 2 Giriwoyo are carried out according to plans that have been prepared . In addition, the purpose of the action taken is to improve students' mathematical thinking abilities achieved.Â Keywords: Realistic Mathematics Approach, Mathematical Thinking Ability